Pengelolaan Data Plasma Nutfah Ternak - nFN Subandriyo (Buletin Plasma Nutfah, 2004)
AbstractThere are several sources of publication could be used as database. The sources could be articles that have been published in the periodicals as well as unpublished data (idle data). Database manager should be the person who know the background, objectives, and the principles to manage the data. In addition, the coordinators should be the persons who have background of animal geneticist by training. Data on the characteristics of breeds or strain within species are extracted and presented on specific format. The format are either in the free or fixed format, for computerization. The presentation could be separated into two form of Master Records containing physical characteristics, and Slave Records containing performance characteristics and environment. Each breed or strain has only one Master Record, but it could have several Slave Records. The number of slave records are dependent upon the number of publication available.AbstrakDi dalam pembuatan pangkalan data (database) yang merupakan bank data, bermacam-macam sumber dapat digunakan, mulai dari artikel yang telah dipublikasi maupun data yang tidak dipublikasi (idle data). Pengelola database harus mengetahui latar belakang, tujuan serta prinsip-prinsip dasar penanganan data. Koordinatornya paling tidak, telah mendapat pendidikan di bidang pemuliaan ternak (animal geneticist by training). Data karakteristik suatu rumpun (breed) atau strain dalam spesies diekstrak dan dipresentasikan dalam suatu format, baik dalam bentuk bebas (free format) maupun tetap (fixed format), sehingga mudah untuk dilakukan komputerisasi. Presentasinya dibedakan menjadi dua, yakni dalam bentuk karakteristik fisik (master record) serta untuk karakteristik performa dan lingkungan (slave record). Setiap rumpun atau strain mempunyai sebuah master record dan beberapa slave record. Jumlah slave record bergantung pada jumlah publikasi yang tersedia.